Reproductive politics and populism: Pentecostal religion and hegemony in the Philippines - Maltese, Giovanni (The Journal of Law and Religion, 2019)
Reproductive politics is the locus classicus for studying the entanglement of religion with politics and lawmaking processes in the Philippines. Although 25 percent of the total population participates in the Pentecostal movement, there is virtually no comprehensive work that studies this movement's attitudes about reproductive health. In this article I analyze Pentecostals' attitude on reproductive health vis-à-vis recent studies that depict the movement as religious populism. I investigate the interests and exclusions that Pentecostals' keywords and narratives, as well as recent scholarship on Pentecostalism, conceal. I first provide a genealogical reconstruction of the debate on reproductive health in the Philippines. Second, I provide an overview of the religious landscape and discuss Pentecostal's attitudes toward reproductive health while demonstrating that their rhetorical positions cannot be understood apart from hegemonic struggles and their entanglement with local and global discourse. Third, I draw theoretical and methodological implications for the study of Pentecostalism, politics, and lawmaking processes in the Philippines. Finally, I conclude by showing the relationship between Pentecostalism in the Philippines and the broader study of religion and politics, including making and implementing law.
CRIS-Team Scopus Importer:2024-03-27
Keywords: hegemony; Pentecostalism; Philippines; populism; reproductive politics